Consent for medical treatment of trans youth / Steph Jowett, Queensland University of Technology. - Jowett, Steph, 1991- (Cambridge bioethics and law., 2022)
Access to medical treatment for trans youth occupies a haphazard and dynamic legal landscape. In this comprehensive scholarly analysis of the historical and current legal principles, Steph Jowett examines the medico-legal nexus of regulation of this healthcare in Australia and in England and Wales. This is informed by an in-depth discussion of the medical literature on treatment for trans youth, including clinical guidelines, the outcomes of treatment and outcomes for trans youth who are unable to be treated. With illustrative examples and clear language, Jowett argues that legal barriers to clinical practice should be congruent with and reflect the current state of medical knowledge. Not only does Jowett assess the extent to which key legal decisions have been consistent with medical knowledge in the past, but she offers a nuanced, comparative perspective that will inform reform efforts in the future.